Approaches for multi-gram scale isolation of enantiomers for drug discovery. (2nd December 2017) - Rossi, Daniela; Tarantino, Marilù; Rossino, Giacomo; Rui, Marta; Juza, Markus; Collina, Simona
ABSTRACT: Introduction : Over the last 30 years, the scientific community has directed its efforts towards the identification of enantioselective approaches to obtain the desired active enantiomer. Accordingly, efficient production of single enantiomers from small to large scale, throughout Drug Discovery (DD) programs, has become of great interest and a fundamental challenge. Areas covered : This review focuses on two fundamental strategies for preparing enantiomers in high yields and with an excellent enantiomeric excess (ee). Separation of racemates, enantioselective synthesis procedures, and integrated approaches have been extensively reviewed, to offer a guide that enables the selection of the suitable methodology for producing pure enantiomers in scales from small to large. Expert opinion : Over the past two decades, drug regulatory agencies have set strict rules on the use of racemates and pure enantiomers, leading to the transformation of the drug market. Indeed, the number of drugs approved as a single enantiomer has exponentially increased, outclassing the racemic compounds. As a consequence, the academia and pharmaceutical companies are eager to develop efficient procedures for obtaining enantiopure compounds on the desired scale.